COMPETITIVE BEHAVIOUR OF COMPONENT CROPS IN SESAME GREENGRAM INTERCROPPING SYSTEMS UNDER DIFFERENT NUTRIENT MANAGEMENT - MANDAL, MALAY KUMAR; PRAMANICK, MAHADEV (The Bioscan, 2014)
Competitive behaviour of component crops in sesame-greengram intercropping systems under different nutrient management was studied on a sandy loam soil at the University of Bidhan Chandra Krishi Viswavidyalaya Mohanpur during summer season for two consecutive years. Under the INM practice the yield of sesame, greengram and sesame equivalent yield were significantly higher (39.63, 18.13 and 30.02%, respectively) than organic nutrient management. Integrated nutrient management the sesame grown in association with greengram appeared to be a dominant crop as indicated by its higher values of land equivalent ratio, monetary advantage, area time equivalent ratio, relative value total, competitive ratio and positive sign of the aggressivity. This indicates that when sesame grown in association with greengram utilized the resources more aggressively in ratio sesame + greengram (2:2) is compared sesame + greengram (2:4). Among the intercrops, greengram proved to be more competitive under integrated nutrient management over the organic nutrient management.